Speed, agility and power potential of young basketball players - Cauševic, D.; Mašic, S.; Doder, I.; Matulaitis, K.; Spicer, S (Baltic Journal of Sport and Health Sciences, 2022)
Background. As basketball constantly evolves, physical performance becomes more and more important. Physical fitness assessments are the most reliable way to find out at what level a basketball player is prepared to perform. Therefore, the main aim of this research was to determine if the speed, agility and power of under-16-year-old (U16) basketball players is related to their playing positions.